Między platonikami z Cambridge a empirystami z The Royal Society - zarys filozofii Josepha Glanvilla - Płoski, Jakub (Studia z Historii Filozofii, 2024)
The article's purpose is to present the views of the 17th-century English philosopher - Joseph Glanvill. They are placed around two main intellectual tendences present in early modern English philosophy. Neoplatonism from the University of Cambridge and the empiricism of the early Royal Society. Discussing the first pool of inspirations, the author points to the typically Platonic elements in his system and the characteristic features of Glanvill’s philosophy, which may place him in the broad tradition of English Latitudinarianism. He then presents the specifics of Glanvill’s skepticism and empiricism. Glanvill’s spiritualist proposals seem to mediate between Cambridge Neoplatonism and the philosophies of the early Royal Society. They were inspired both by the specific understanding of spirit found in More’s Neoplatonic metaphysics and by certain thoughts present among early modern naturalists. In general presentation, Joseph Glanvill’s philosophical views appear as a synthesis of elements characteristic of these two approaches.